THE INFLUENCE OF INITIAL PRESSURE ON THE CONCRETE COMPRESSIVE STRENGTH - Lina Flaviana Tilik (PILAR, 2011)
This study is aimed to find out the influence of initial pressure and the percentage of fly ash as partial substitution of cement on the value of concrete compressive strength. The test object used is cylindrical with a diameter 10 cm and a height of 20 cm. This study used independent variables of initial pressure of 25 kg/cm², 50 kg/cm², and 75 kg/cm², and dosages of fly ash of 5%, 10%, 15% and 20%. The concrete compressive strength with initial pressure is higher than which without initial pressure. The percentage of fly ash 5%, 10%, 15% and 20% given lower concrete compressive strength than the normal.  The result of study  that the composition of concrete mixture which is given an initial pressure of 75 kg/cm² produces a highest compressive strength is 41,08 MPa.